The Kindergarten as an Enlightening Flame That Carries the Eternal Truths of Life Over the Years - Akseniya Tileva (Педагогически форум)
Review of Lilia Dimitrova's book "The beginning of preschool education - the city of Kazanlak against the background of the general historical process"